SuessR: Regional corrections for the effects of anthropogenic CO2 on δ13C data from marine organisms. Issue 8 (19th May 2021) - Clark, Casey T.; Cape, Mattias R.; Shapley, Mark D.; Mueter, Franz J.; Finney, Bruce P.; Misarti, Nicole
Abstract: Anthropogenic CO2 emissions associated with fossil fuel combustion have caused declines in baseline oceanic δ 13 C values. This phenomenon, called the Suess effect, can confound comparisons of marine δ 13 C data from different years. The Suess effect can be corrected for mathematically; however, a variety of disparate techniques are currently used, often resulting in corrections that differ substantially. SuessR is a free, user‐friendly tool that allows researchers to calculate and apply regional Suess corrections to δ 13 C data from marine systems using a unified approach. SuessR updates existing methods for calculating region‐specific Suess corrections for samples collected from 1850 to 2020. It also estimates changes in phytoplankton 13 C fractionation associated with increasing water temperature and aqueous CO2 concentrations, referred to here as the Laws effect. SuessR version 0.1.3 contains four built‐in regions, including three in the subpolar North Pacific (Bering Sea, Aleutian Islands and Gulf of Alaska) and one North Atlantic region (Subpolar North Atlantic). Users can also supply environmental data for regions not currently built into SuessR to generate their own custom corrections. In 2020, net corrections (Suess + Laws corrections) were as follows—Bering Sea: 1.29‰; Aleutian Islands: 1.30‰, Gulf of Alaska: 1.30‰; and Subpolar North Atlantic: 1.31‰ (compared to a global atmospheric CO2 change of ~2.43‰ across the same period). For samples collected in 2020, the net correction exceeds instrumental error (±0.2‰) when making comparisons across only eight years (i.e. 2013–2020). The magnitude of the Suess effect calculated by SuessR aligns with published estimates, whereas the Laws effect is smaller than previously calculated, resulting from updated estimates of average community cell sizes, growth rates and permeability of phytoplankton plasmalemmas (the plasma membrane which bounds the cell) to CO2 . The increasing magnitude of the Suess effect means this phenomenon is no longer only of concern to historical ecologists, but now affects contemporary ecological studies using δ 13 C data. This highlights the importance of a unified approach for generating Suess corrections. The SuessR package provides a customizable tool that is simple to use and will improve the interpretability and comparability of future stable isotopic studies of marine ecology. ​